The forming of valuable orientations in the process of physical up-bringing - Bezverhnya G.V; Mayevskiy N.Y (Kharkov National Pedagogical University, 2010)
In the article we consider the impact of physical education as an academic subject in the formation of value orientations of students. Value orientations are formed in the face of social experience and reflects in aims, beliefs, ideals, interests. Therefore, special attention should be paid to in fluences on values orientations formation mechanisms to solve the motivational impact on the consciousness and behavior of the individual, the system of education and training. The development of physical culture values enables a young person to understand the complexity of life, to form physical and spiritual potential. Practical application of research, value orientations in the field of physical culture has an important achievement of the aims in the future professional activity.